The Movement to Protect Local Values in Germany’s Lusatia Region - Jonda, Bernadette (Górnośląskie Studia Socjologiczne. Seria Nowa, 2014)
The article discusses the important aspects of the Sorbian minority’s existence in Lusatia, in two German eastern states (Saxony and Brandenburg), in the context of the risk for the population of the region stemming from the activities pertaining to brown coal mining, which entail the need for resettlement of the population and the subsequent liquidation of their villages. Regarding this background, the author presents the dilemmas of the inhabitants of the region, who are, on the one hand, filled with concern for the protection of natural environment and the desire to save the homeland from destruction, but, on the other hand, are aware of the need to invest in energy. The strong commitment to cultural continuity of the Sorbs goes hand in hand with developed plans for the creation of the modern conditions of life. The text refers to the UNESCO Convention for the Safeguarding of the Intangible Cultural Heritage and the legal status of the Sorbs. It also includes analysis of the attitudes of residents threatened by the need of resettlement. This analysis is based on qualitative and quantitative research carried out by the author in 2010 in the village of Rohne. It identifies five types of different approaches, behind which the various motives are to be considered. Particularly noteworthy is the treatment of space (territory, home), the value of which cannot simply be moved to another location.